1983
DOI: 10.1203/00006450-198304000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Oxygenation Determines Autoregulation of Cerebral Blood Flow in the Fetal Lamb

Abstract: Summary MATERIALS AND METHODSWe examined autoregulation of cerebral blood flow (CBF) over the range of oxygen tension commonly observed in the chronic fetal lamb preparation. Seventeen animals were surgically prepared under general anesthesia for chronic in utero studies. ~a s e d on measured resting arterial Po2 and calculated % saturation 24-48 h after surgery, two groups were defined: a normoxic group of eight with saturation of 57% or higher (our laboratory normal for physiologically stable preparations) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 0 publications
4
47
1
Order By: Relevance
“…In fetal lambs, a 20% reduction in blood volume was accompanied with decreases in blood pressure of 21 %, in cardiac output of 40%, and in CBF of 18% when corrected for the 4-tom increase in Pco2 which occurred (39). In other studies, autoregulation was observed in normoxic fetal lambs as blood pressure ranged from 42 to 6 1 mm Hg (38). A 26% mean decrease in arterial blood pressure resulted in no significant change in total or regional brain blood flow (38).…”
Section: Cardiac Output (Mlomin-'kg Body-')mentioning
confidence: 80%
See 1 more Smart Citation
“…In fetal lambs, a 20% reduction in blood volume was accompanied with decreases in blood pressure of 21 %, in cardiac output of 40%, and in CBF of 18% when corrected for the 4-tom increase in Pco2 which occurred (39). In other studies, autoregulation was observed in normoxic fetal lambs as blood pressure ranged from 42 to 6 1 mm Hg (38). A 26% mean decrease in arterial blood pressure resulted in no significant change in total or regional brain blood flow (38).…”
Section: Cardiac Output (Mlomin-'kg Body-')mentioning
confidence: 80%
“…In other studies, autoregulation was observed in normoxic fetal lambs as blood pressure ranged from 42 to 6 1 mm Hg (38). A 26% mean decrease in arterial blood pressure resulted in no significant change in total or regional brain blood flow (38).…”
Section: Cardiac Output (Mlomin-'kg Body-')mentioning
confidence: 99%
“…The sheep fetus displays cerebral hemodynamics similar to humans and permits repeated physiological measurements in utero in the unanesthetized state. Importantly, similar to the human fetus [77][78][79][80], the fetal sheep displays a very limited range of cerebral autoregulation under normal conditions and a pressure-passive cerebral circulation when subjected to systemic hypoxia and associated hypotension [66,[81][82][83][84]. Moreover, measurements of BP, electroencephalography, blood oxygenation, and other vital variables can be correlated with acute changes in cerebral blood flow and metabolism.…”
Section: Hypoxia-ischemia In Fetal Sheep Generates Pathological Featumentioning
confidence: 99%
“…The importance of the central autonomic system and adrenal stress hormones remains unclear, as well as the systemic blood concentrations of metabolic substrates, such as glucose and products such as lactate. The fetal sheep brain, in particular when immature and hypoxemic, has essentially no ability to autoregulate [81][82][83]. Hence, in umbilical cord occlusion models, the fall in BP exacerbates the fetal brain hypoxia with a consequent reduction in CBF that leads to partial ischemia.…”
Section: Pathophysiological Mechanisms Of Wmi Related To the Brachiocmentioning
confidence: 99%
“…Experiments on fetal lambs have shown that even acute, short-term hypoxia can affect cerebral autoregulation. Oxygen saturation at 50% lasting longer than 10 minutes has been shown in a global abolition of cerebrovascular autoregulation for several hours (35,36). Furthermore, impaired oxygen transfer across the placenta (e. g. in placental abruption) is one of the common causes of the loss of cerebral autoregulation in neonates, and autoregulation seems to be more vulnerable than other regulatory mechanisms for the cerebral circulation (37).…”
Section: Fetal Hypoxia and Cerebrovascular Autoregulationmentioning
confidence: 99%